A framework for design wind loads on air-permeable multilayer cladding systems - Miller, Connell S.; Kopp, Gregory A. (Frontiers in Built Environment, 2024)
Air-permeable multilayer cladding (vinyl siding, roof pavers, discontinuous metal roofing, solar panels, etc.) are one of the most common types of building components in North America. Their defining aerodynamic feature is that they have an air cavity separating the component from the sheathing, studs, interior layer. Due to air-permeability, external wind loads can transfer into the air cavity between the layers. Although these cladding systems have similar geometries in many ways, design loads are not generally available for such systems. This study aims to synthesize the available literature on the pressure equalization factor, which is the proportion of external load acting on the cladding and provide a framework for design wind loads on air-permeable multilayer cladding systems. To accomplish this, the many factors that affect the pressure equalization factor, such as the gap-to-cavity-depth ratio, panel size, and exposure are discussed. Then, the pressure equalization factors from multiple studies are combined to examine the effect of effective area on the pressure equalization factor. Finally, recommendations for implementing these guidelines into design standards are provided.